Associations between body composition profile and hypertension in different fatty liver phenotypes - Huang, Xiaoyin; Zeng, Yuchen; Ma, Mingyang; Xiang, Liangguang; Liu, Qingdan; Xiao, Ling; Feng, Ruimei; Li, Wanxin; Zhang, Xiaoling; Lin, Moufeng; Hu, Zhijian; Zhao, Hongwei; et al. (Frontiers in Endocrinology, 2023)
Background It is currently unclear whether and how the association between body composition and hypertension varies based on the presence and severity of fatty liver disease (FLD). Methods FLD was diagnosed using ultrasonography among 6,358 participants. The association between body composition and hypertension was analyzed separately in the whole population, as well as in subgroups of non-FLD, mild FLD, and moderate/severe FLD populations, respectively. The mediation effect of FLD in their association was explored. Results Fat-related anthropometric measurements and lipid metabolism indicators were positively associated with hypertension in both the whole population and the non-FLD subgroup. The strength of this association was slightly reduced in the mild FLD subgroup. Notably, only waist-to-hip ratio and waist-to-height ratio showed significant associations with hypertension in the moderate/severe FLD subgroup. Furthermore, FLD accounted for 17.26% to 38.90% of the association between multiple body composition indicators and the risk of hypertension. Conclusions The association between body composition and hypertension becomes gradually weaker as FLD becomes more severe. FLD plays a significant mediating role in their association.